Functional Characterization of SMG7 Paralogs in Arabidopsis thaliana - Capitao, Claudio; Shukla, Neha; Wandrolova, Aneta; Mittelsten Scheid, Ortrun; Riha, Karel (Frontiers in Plant Science, 2018)
SMG7 proteins are evolutionary conserved across eukaryotes and primarily known for their function in nonsense mediated RNA decay (NMD). In contrast to other NMD factors, SMG7 proteins underwent independent expansions during evolution indicating their propensity to adopt novel functions. Here we characterized SMG7 and SMG7-like (SMG7L) paralogues in Arabidopsis thaliana. SMG7 retained its role in NMD and additionally appears to have acquired another function in meiosis. We inactivated SMG7 by CRISPR/Cas9 mutagenesis and showed that, in contrast to our previous report, SMG7 is not an essential gene in Arabidopsis. Furthermore, our data indicate that the N-terminal phosphoserine binding domain is required for both NMD and meiosis. Phenotypic analysis of SMG7 and SMG7L double mutants did not indicate any functional redundancy between the two genes, suggesting neofunctionalization of SMG7L. Finally, protein sequence comparison together with a phenotyping of T-DNA insertion mutants identified several conserved regions specific for SMG7 that may underlie its role in NMD and meiosis. This information provides a framework for deciphering the non-canonical functions of SMG7-family proteins.